PRODUKSI BERAS KEMASAN PERSPEKTIF MANAJEMEN BISNIS ISLAM - Abdul Latif (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2019)
Production is a human activity to produce goods and services which is then used by consumers. While Islamic business management is idea about how to regulate, manage, and run a business or convenient business with Islamic sharia.The Production process of packed rice that happened to UD Albas Jaya through several processes, start from the search for raw materials to packaging.In passing all these stages should be done properly and correctly as taught by the Islamic religion. This study intends to determine (1) the production process of packed rice at UD Albas Jaya Putih Village, Gampengrejo District, Kediri Regency, (2) knowing the process of packed rice production at UD Albas Jaya Putih Village, Gampengrejo District, Kediri Regency, in terms of Islamic business management. This study used qualitative approach to the type of case study research in the field and descriptive research design. The informants in this study arePacked rice producers, employees and surrounding communities and agents. The method of data collection in collecting data used observation and interview. As for data analysis using data reduction, data presentation, and drawing conclusions. The results of this study indicate that there are several production processes at UD Albas Jaya, including; First, preparation of raw materials (grain) that prioritizes good quality rice, by way of business owners going down to the field to make the selection of raw materials, then if the price of raw materials rises the producers do not increase the prices of their products. Second, the process of breaking the skin, does not cause environmental pollution because the waste can be resold. Third, the process of polishing rice, in addition to polishing rice which is still new, UD Albas Jaya also polishes rice that has not been sold for a long time to appear white again. Fourth, the packaging process, mixing old rice with new rice, as well as imperfect in weighing.fifth, the storage process.See from the production process, the production process of UD Albas Jaya is not in accordance with Islamic business management, because there are still production behaviors that are not in accordance with Islamic business management principles such as; polish old rice to make it look white again, mix new rice with old rice, and less to perfect the scales.